Identification, characterization, and statistical analysis of mudstone aggregate clasts, Cretaceous Carlile Formation, Central Alberta, Canada. (June 2017) - Laycock, Dallin P.; Pedersen, Per Kent; Montgomery, Benjamin C.; Spencer, Ronald J.
Abstract: While clastic mudstones and shale were traditionally interpreted to have been deposited in quiet water settings, recent flume experiments and studies have shown that mud can be transported in and deposited by traction currents as migrating ripples of mud aggregates. Despite these recent advances, mud aggregates have rarely been adequately described in the rock record. These mud aggregates and the sedimentary structures they form in mudstone successions are difficult to observe in the rock record due to compaction, which often obliterates the aggregates and flattens bedforms. This paper documents unambiguously identifiable sand sized mudstone aggregates in thin sections and SEM, transported in traction, and deposited in a series of prograding clinothems. These aggregates were sufficiently indurated to locally preserve shelter porosity, significantly improving the hydrocarbon reservoir properties. Grain size analysis of the aggregates was performed on thin sections, as well as disaggregated samples measured by a laser diffraction grain size analyzer for comparison. These analyses showed that sand sized aggregates often comprise more than half of the sediment volume. While the clay-rich composition of the Carlile Formation would suggest that it is a mudstone, statistical analysis of these grain size measurements show that it could alternatively be described as a silty sandstone. These findings potentially change how we think about mudstone classification, fine-grained sedimentation, and mudstone dominated petroleum reservoirs. Graphical abstract: Highlights: Clay-rich mudstone contains sand sized mud aggregates visible in thin section. Grain size analysis suggests this unit could be classified as a muddy sandstone. Aggregate clasts sufficiently indurated to locally preserve intergranular porosity.